Brno opět žije na Veveří - Cejpová, Pavlína (Vysoké učení technické v Brně. Fakulta architektury, 2023)
Tato práce se zabývá návrhem dvou bytových domů a přilehlých prostorů. Rozvíjí se tím předchozí architektoniko-urbanistická studie prostoru u městské třídy Veveří. V domech se nacházejí byty dispozic od 1kk po 4kk. Domy vytváří hranici nově navrženého veřejného prostoru. Proto jsou v parteru kromě domovních zázemí navrženy i komerční jednotky. Byť se domy nacházejí na nároží, nelze říci, že se jedná o zcela typické nárožní domy. Práce se snaží naplnit téma života na městské třídě Veveří, která je v řešeném místě neatraktivní.

This thesis deals with the design of two apartment buildings and adjacent public spaces. This thesis develops the previous architectural-urbanistic study of the space near the city street Veveří. The houses have variaous apartements ( from units with 1 bedroom to units with 3 bedrooms). The houses form the boundary of the newly designed public space. Commercial units are designed on the ground floor as well as housing facilities. Although the houses are located on a corner, it cannot be said that these are completely typical corner houses. The work tries to fulfill the theme of life on the city street Veveří, which is unattractive in the location.
Brno lives on Veveří again
Keywords: městská třída; Veveří; byt; veřejný prostor; nárožní dům; chráněný strom; platan; city street; Veveří; apartement; public space; corner house; protected tree; plane tree